Dampak Profesi Tenaga Kerja Indonesia Terhadap Keharmonisan Keluarga - Fadhil Hardiansyah; Al Mujahidah Layal Anhur; Dinny Rahmayanty (TERAPUTIK: Jurnal Bimbingan dan Konseling, 2024)
Indonesian workers or migrant workers could be interpreted as someone who will, is working and has been working abroad outside their country of origin, whether they meet the requirements or not and through legal or illegal channels.  A person who travels abroad to work is referred to as a TKI.  Becoming a TKI can have an impact on the family, especially harmony. This research aims to determine the impact of TKI on family harmony in Kampung Kotagajah.  Field research is the type of research that used in this thesis, using the nature of qualitative descriptive research.  Research in this thesis used the data collection techniques in the form of interview and documentation. The interview were conducted with the village apparatus from Kotagajah , Bayan Kampung Kotagajah, five people who became TKIs, the TKI families, and the local environment. based on research results, the factors that encourage the society of Kampung Kotagajah to work abroad is the low of economic.  The impact that appears on the TKI family in the are positive and negative. Meanwhile, from the positive impact is that the family's economic situation improves, while disputes, infidelity, lack of affection for children to divorce are the negative impacts of TKI on families.